2002
DOI: 10.1364/ol.27.000173
|View full text |Cite
|
Sign up to set email alerts
|

Near-field probing of active photonic-crystal structures

Abstract: We report a study of the optical near field of an active integrated component operating near the 1.55-mum telecommunications wavelength. The device is based on a two-dimensional photonic crystal etched in a suspended InP membrane. Topographic as well as optical information is collected by use of a scanning near-field optical microscope in collection mode, providing information about the local distribution of the losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…21 The SNOM imaging of photoluminescence in a 2D PC etched in a suspended InP membrane has also been reported. 22 However, the potential of this technique to map the intensity distribution of ͑bound͒ modes guided along PCWs has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%
“…21 The SNOM imaging of photoluminescence in a 2D PC etched in a suspended InP membrane has also been reported. 22 However, the potential of this technique to map the intensity distribution of ͑bound͒ modes guided along PCWs has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%
“…1a Since NSOM is considered as a very effective tool for the study of mode properties in PC cavities [7][8][9], the additional control of the emission energy of QD in the range of hundreds of meV, provided by the nanoindentation regime, create a very attractive way of spectral matching of the quantum dot exciton and the cavity mode. Below we will present some preliminary results directed towards realisation of such experiments.…”
Section: Emission Spectra Of Qd Structures Nsom Spectra Of Structuresmentioning
confidence: 99%
“…However, µPL lacks the spatial resolution needed to study the spatial coupling between QD and PhC cavity, which plays a key role in parameters such as the Rabi frequency and the Purcell factor. Scanning near-field optical microscopy (SNOM) has been used to characterize PhC cavities at room temperature [2][3][4][5][6][7][8] and single QDs at low temperatures. [9][10][11][12] However, near-field studies of the coupling of single QDs to PhC cavity modes have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%